2014
DOI: 10.1097/jim.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Why We Need Community Engagement in Medical Research

Abstract: Background The medical research enterprise depends on public recognition of its societal value. In light of evidence indicating public mistrust, especially among minorities, inadequate enrollment and diversity of research participants, and poor uptake of findings, medical research appears to fall short of sufficient public regard. Community engagement in medical research, with special attention to minority communities, may help to remedy this shortfall by demonstrating respect for communities in practical ways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
143
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 32 publications
4
143
0
Order By: Relevance
“…), as found by Roosa et al (2008) or in different countries such as the South Asian populations in UK, or North Africa populations in central Europe as found by Khan et al (2019) as well as Waheed et al (2015). Previous research highlights the importance of engaging communities in the research process in order to improve the quality of care (Holzer et al 2014;Eyles et al 2016). It has been suggested that recruitment and development of eHealth and mHealth interventions should be designed to systematically address the health inequalities of a wider range of minorities or underserved populations in a community (e.g.…”
Section: Ehealth Mhealth and Community Health Inequalitiesmentioning
confidence: 92%
“…), as found by Roosa et al (2008) or in different countries such as the South Asian populations in UK, or North Africa populations in central Europe as found by Khan et al (2019) as well as Waheed et al (2015). Previous research highlights the importance of engaging communities in the research process in order to improve the quality of care (Holzer et al 2014;Eyles et al 2016). It has been suggested that recruitment and development of eHealth and mHealth interventions should be designed to systematically address the health inequalities of a wider range of minorities or underserved populations in a community (e.g.…”
Section: Ehealth Mhealth and Community Health Inequalitiesmentioning
confidence: 92%
“…Therefore, one way of assessing the adequacy of a consent process is the extent to which it expresses respect, and well as considering alternative activities that express respect. For example, the concept of respect is central to the rise of community engaged research and patient oriented outcomes research (Ross et al 2010; Holzer et al 2014. ; Woolf et al 2016).…”
mentioning
confidence: 99%
“…13 This lack of trust can prevent communities from understanding the social benefits of research and prevent its members from enrolling in studies. 14 These entwined American histories-of race-based discrimination and of abuse in biomedical research-form the backdrop to Johns Hopkins's own history and context. Johns Hopkins is located in Baltimore, the sixth poorest city in the United States, with 24 percent of its adults and 37 percent of children living in poverty.…”
Section: Reasons For Mistrust In Biomedical Researchmentioning
confidence: 99%
“…but may also help specifically to build trust, encourage participation, and promote the uptake of findings," and therefore community engagement enhances the efficacy of research affecting particular populations. 40 While community engagement has seen significant successes, it is imperfect, and its methods could be better developed and more stringently implemented. 41 Moreover, there is an unfortunate tendency for researchers and research institutions to minimize or ignore the asymmetries in power that are intrinsic to their relationships with community constituents.…”
Section: Possible Social Harms Of Institutional Decisions About Genetmentioning
confidence: 99%